Assessment on infection prevention and control knowledge among medical professionals in south Indian population - Radhakrishnan, Rahul; Datchanamoorthy, Maheswary; Narayanasamy, Damodharan; Leela, Kakithakara Vajravelu (The Journal of Infection in Developing Countries, 2023)
Introduction: Healthcare workers are always at higher risk of biological exposure as the healthcare setting is hazardous, and it is impracticable to exclude infection. Poor compliance with standard precautions among healthcare workers is one of the leading causes of healthcare-associated infections. This study analyzed the gaps in knowledge, attitude, and practice of infection control among healthcare workers and the influence of the COVID-19 pandemic, internet, and social media usage on infection control. Methodology: A cross-sectional study was conducted from 1st to 31st March 2022 among various healthcare professionals using a self-administered structured questionnaire to evaluate knowledge, attitude, and practice on infection control. The impact of COVID-19, Internet, and social media usage on infection control practices was also analyzed. Results: Among 382 healthcare workers who participated in the study, 89.4% of the participants had good knowledge, 55.26% had a neutral attitude, and all showed good practice levels on infection control. Similarly, the result showed that internet and social media usage during COVID-19 had significantly enhanced the knowledge, attitude, and practice on infection control. Conclusions: Healthcare professionals must be frequently updated on infection control guidelines and routine training programs. The hospital's adherence to the Joint Commission International (JCI) guidelines reduces the risk of healthcare-associated infections. As observed in this study, due to the prominent influence of social media and the internet, these platforms can be exploited to provide training and awareness to healthcare professionals and the public.